Hausa-Yoruba Relations 1500-1800: A Historical Perspective (2007)
From a revisionist perspective, this paper demonstrates that the history of Old Oyo empire and Hausa-city states were closely interwoven especially in commercial interaction, cultural exchange, the propagation of Islam and state building processes. The paper argues that the articles of trade suggest that beyond the movement of goods and peoples in both societies, an enormous degree of diplomacy and politics existed to facilitate the process of exchange. The relationship between Old Oyo and Hausa-city states was closely linked to the political economy of the states especially slave trade, export and import of horses, cowries and firearms. It is then argued that the relationship was more complex and mutually reinforcing. Contrary to widespread accounts, there is no material to show that the term Yoruba was originally used by the Hausa to describe the people of Oyo-ile. There is every possibility that the people of Oyo ile whose language was Yoruba described themselves as such. The first reference to the term Yoruba could be found in the work of the famous Songhay scholar, Ahmad Baba Al-Timbukti.